Lipid droplet associated protein HILPDA promotes hypoxia-induced ferroptosis by driving LPCAT3-mediated polyunsaturated phospholipids enrichment - Zhenmei Song; Wenli Li; Jie Zeng; Xuexin Wang; Dezhi Wang; Xingchen Liao (PLoS ONE, 2026)
Each year, tens of millions of individuals sojourn to high-altitude environments (>2500 m), where they face the significant physiological challenge of hypoxia, a condition that often induces a range of gastrointestinal disorders. While our prior studies linked this damage to ferroptosis, the role of hypoxia-inducible lipid droplet-associated protein (HILPDA), a hypoxia inducible factor-1α/2α (HIF-1α/2α) downstream regulator, in this process remains unclear. This study aimed to explore the role and mechanism of HILPDA in regulating ferroptosis of normal human gastric and small intestinal epithelial cells (NGEC and HIEC) under hypoxic conditions. Our results found that overexpression of HIF-1α, HIF-2α, and HILPDA exacerbated hypoxia-induced cell death, which was reversed by the ferroptosis inhibitor ferrostatin-1. Knockdown of HIF-1α/2α inhibited HILPDA expression. Furthermore, knockdown of HILPDA led to a reduction of the hypoxia-induced lipid peroxidation, and the ferroptotic characteristics of cellular mitochondria observed under transmission electron microscopy. Conversely, HILPDA overexpression reversed the protective effects of HIF-1α/2α knockdown. Lipidomic analysis further revealed that HILPDA knockdown significantly decreased the levels of polyunsaturated fatty acid-phosphatidylcholines (PUFA-PCs) and phosphatidylethanolamines (PEs) under hypoxia. Compared to HIF-1α knockdown, HILPDA knockdown led to a slight difference in PUFA-PEs without significant difference in PCs and phosphatidylinositols (PIs) under hypoxia. Compared to HIF-2α knockdown, HILPDA knockdown resulted in negligible differences in PEs, PCs, and PIs. In addition, HILPDA knockdown downregulated Lysophosphatidylcholine Acyltransferase 3 (LPCAT3), and overexpression of LPCAT3 significantly attenuated the inhibitory effect of HILPDA knockdown on hypoxia-induced ferroptosis. In conclusion, HILPDA enhanced susceptibility to hypoxia-induced ferroptosis in NGEC and HIEC by enriching PUFA-containing phospholipids through LPCAT3. These findings identified the HIF-1α/2α-HILPDA-LPCAT3 axis as a pivotal pathway driving hypoxia-induced ferroptosis, therefore providing potential therapeutic targets for gastric and small intestinal mucosal injury associated with hypoxia.